Reversible blindness in cryptococcal meningitis with human immunodeficiency virus infection - Gupta, Manisha; Kumar, Abhishek; Kumar, Angad; Mathur, Vaibhav (International Journal of Research in Medical Sciences, 2024)
Ocular complications in cryptococcal meningitis (CM) are commonly attributed to elevated intracranial pressure (ICP). We report a case of reversible vision loss complicating acquired immunodeficiency syndrome (AIDS) related to CM with a normal ICP. The patient had sudden onset painless blindness during the anti-retroviral therapy (ART) and anti-fungal therapy. On evaluation, clinical and radiological findings of optic neuritis were present. While reviewing the literature for causes of blindness in CM, we concluded the cause was optic neuritis due to immune reconstitution inflammatory syndrome (IRIS) because of concomitant ART intake by the patient. We witnessed dramatic visual improvement after the use of systemic corticosteroids. The potential significance of this case report is to highlight the possible role of corticosteroids in the prevention of blindness due to CM.